Do Post-Operative Electrocardiographic (ECG) Changes Indicate any Underlying Graft Problem after CABG? Correlation of Early Post-Operative ECG Changes with CT Coronary Angiography (CTCA) - Potnis, Abhishek Rajendra; Potwar, Sushrut Suhas; Aironi, Balaji; Kulkarni, Dwarkanath Vivekanand; Jadhav, Uday Eknath; Sawant, Gaurish Omprakash (Cardiology and Cardiovascular Medicine, 2023)
Purpose: Identifying occult and potentially life-threatening problems in the absence of hemodynamic instability and elevation of cardiac markers has always remained a diagnostic challenge in patients after coronary artery bypass graft (CABG). A study to identify these threats by comparing ECG changes to CTCA changes is thus essential to isolate and evaluate highrisk cases. Methods: First 45 post-CABG patients having ECG changes at the 0th, 4th, 18th hour, and follow-up were subjected to computed tomography coronary angiography (CTCA), and results were evaluated using the Chisquare test to establish a correlation. Results: Absolute high-risk and relative high-risk profiles of patients were established in the present study. Patients with EF 50-60%, with native right coronary involvement and graft to posterior left ventricular (PLV) artery are at absolute risk of having ECG changes translated into CTCA changes. Conclusion: The study addresses the quintessential question ‘which ECG changes in the postoperative period should be given immediate attention and which ones can be safely ignored?’